2000
DOI: 10.1159/000054132
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis: Leukocyte Rheology at Baseline and after in vitro Activation

Abstract: We evaluated leukocyte rheology, expressed as leukocyte filtration, polymorphonuclear (PMN) membrane fluidity and cytosolic Ca2+ concentration in subjects with acute deep venous leg thrombosis (DVT). In 14 subjects with leg DVT we examined the leukocyte filtration [unfractionated, mononuclear cells (MN), PMNs], PMN membrane fluidity and PMN cytosolic Ca2+ concentration. Subsequently, we evaluated the same PMN variables after in vitro chemotactic activation with 4-phorbol-12-myristate-13-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In previous papers regarding several venous diseases, such as deep venous thrombosis [9,19], post-thrombotic syndrome [7,8] and leg venous ulcers [20], we demonstrated, especially after in vitro activation with 4-phorbol 12-myristate 13-acetate (PMA) and with N-formyl-methionyl-leucyl-phenilalanine (fMLP), an evident alteration of the two parameters that reflect the rheology of the polymorphonuclear cells: the membrane fluidity, examined employing the fluorescent probe TMA-DPH, and the cytosolic calcium concentration, explored using the fluorescent probe Fura-2AM. In subjects with deep venous thrombosis [9] and leg venous ulcers [20] we also found an altered profile of the polymorphonuclear integrins (CD11a, CD11b, CD11c and CD18) at baseline and after activation with PMA and fMLP.…”
Section: Discussionmentioning
confidence: 99%
“…In previous papers regarding several venous diseases, such as deep venous thrombosis [9,19], post-thrombotic syndrome [7,8] and leg venous ulcers [20], we demonstrated, especially after in vitro activation with 4-phorbol 12-myristate 13-acetate (PMA) and with N-formyl-methionyl-leucyl-phenilalanine (fMLP), an evident alteration of the two parameters that reflect the rheology of the polymorphonuclear cells: the membrane fluidity, examined employing the fluorescent probe TMA-DPH, and the cytosolic calcium concentration, explored using the fluorescent probe Fura-2AM. In subjects with deep venous thrombosis [9] and leg venous ulcers [20] we also found an altered profile of the polymorphonuclear integrins (CD11a, CD11b, CD11c and CD18) at baseline and after activation with PMA and fMLP.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines can be classified into four classes; CXC, CC, C and CX3C according to their structure. Previous studies have shown that a polymorphonuclear (PMN) activation in thrombosis is present, and that PMN activation may be important in the etiologies of thrombosis (14,15). CXC chemokines possess a potent chemotactic activity on neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that leukocytes and erythrocytes play a role in the process of coagulation [3][4][5][6][7][8][9][10] and their presence is clearly observed in the anatomy of a venous clot, which consists of a laminar structure of erythrocytes and fibrin, permeated by large numbers of leukocytes. 11 A recent study, using a mouse model of flow restriction-induced deep vein thrombosis without endothelium damage, showed that blood monocytes and neutrophils provide an initiating stimulus for development of deep vein thrombosis.…”
Section: Introductionmentioning
confidence: 99%